(3eYGOdI GdMjGI (B:s (3cja fMUd Ydi GdbhI GdPGJjI (B/s - Sinelnikov, Valery; (3GdHGcjQ, SYjO(B,s ((3GdbGgQI (B:s (3OGQ YdGA GdOjf ddfTQ hGdJhRjY(B,s, 2016)
(3jJfGhd GdcJGH ehVhY GcJSGH GdbhI GdTNUjI hWGbI GdMjGI, hjfGbT WQjbjf dHdhZ GdceGd(B: (3WQjb GdeYGfGI hWQjb GdeYQaI, eY GdJQcjR Ydi JZjjQ GdWHY hGdCacGQ dJMSjf LhOI GdMjGI(B.s
Translation of: Uravnenie zhizni (Russian).
Keywords: Self-actualization (Psychology); Conduct of life; Vitality